Which factors influence the need for inpatient rehabilitation after severe trauma?. Issue 12 (December 2016) - Debus, Florian; Lefering, Rolf; Lang, Nils; Oberkircher, Ludwig; Bockmann, Benjamin; Ruchholtz, Steffen; Kühne, Christian Alexander; the TraumaRegister DGU,
Abstract: Introduction: Despite the importance of rehabilitation in the treatment of patients with severe trauma or even of severely injured patients, the cooperation between acute and rehabilitation hospitals is often inadequate. The present study aims to identify factors that make it probable that a severely injured patient requires inpatient rehabilitation following the acute treatment. Material and methods: A retrospective analysis of 75.357 cases from the TraumaRegister DGU ® (TR-DGU) was performed. All cases from 2002 until 2013 with an ISS ≥ 9, who were taken to the ICU were included. Regarding the discharge destination the subgroups "at home" and "rehabilitation hospital" were analyzed in detail. Finally, we performed a multivariate regression analysis based on the parameters previously collected. Results: 24.208 patients (32.1%) were transferred to a rehabilitation clinic. In the multivariate regression analysis the most relevant independent parameters for discharge in a rehabilitation hospital were age (18–54: OR 1.65; 55–74: OR 2.86 and 75 and older: OR 5.07, all p ≤ 0.001), AIS pelvis ≥ 2 (OD 1.94), AIS legs (OR 2.02), AIS spine (AIS 4: OR 5.78 and AIS 5–6: OR 6.36) and the AIS head (AIS 3: OR 1.88; AIS 4: OR 3.11 and AIS 5–6: OR 7.55) (all p ≤ 0.001). The length of stay in the ICU (3–7 days: OR 1.88; 8–28 Days: OR 5.42 and 29 and more days: OR 14.7, all p ≤ 0.001) was also a relevant parameter. The overall ISS presented no relevant influence with an OR of 1.02 (p = 0.03). Discussion and conclusion: Knowing independent factors for a required inpatient rehabilitation helps the treating physicians to identify the patients at an early stage in acute hospitals. So the transfer to a rehabilitation clinic can be organized faster and more selective in future.